Community Empowerment Through Effective Leadership For Achieving Organizational Vision In Educational Institutions In Suryalaya - Iwan Saputra; R. Hozin Abdul Fatah; Lati Sari Dewi; Siti Amirah Makarim; Sani Haryati; Zalu Nabil Yassin Iswara; Ruslan; Sufi Halwani (CV. SINAR HOWUHOWU, 2025)
Organizational vision serves as a strategic compass that directs all elements of an institution toward long-term goals. However, without effective leadership, the process of internalizing and operationalizing this vision often fails to reach its full potential. This community service initiative aimed to strengthen the capacity of educational personnel in pesantren-based institutions in Suryalaya by developing their understanding and application of effective leadership principles. The intervention employed participatory approaches through interactive workshops, group discussions, and strategic planning simulations. Thirty education staff members from various institutions took part in the program, representing roles from school leadership to teaching and administration. The results showed a significant increase in the participants’ ability to articulate their organizational vision, identify key performance indicators, and develop actionable leadership strategies. Post-activity evaluation indicated that 90% of participants considered the program useful and applicable to their institutional context. This program highlights the importance of aligning leadership capacity with the organizational vision to foster institutional resilience and progress.